Seismic performance of wood-frame houses in south-western British Columbia. - Goda, Katsuichiro
The seismic performance of conventional wood-frame structures in south-western British Columbia is analytically investigated through incremental dynamic analysis by utilizing available UBC-SAWS models, which were calibrated based on experimental test results. To define an adequate target response spectrum that is consistent with information from national seismic hazard maps, record selection/scaling based on the conditional mean spectrum (CMS) is implemented. Furthermore, to reflect complex seismic hazard contributions from different earthquake sources (i.e. crustal events, interface events, and inslab events), we construct CMS for three earthquake types and use them to select and scale an adequate set of ground motion records for the seismic performance evaluation. We focus on the impacts of adopting different record selection criteria and of using different shear-wall types (Houses 1-4; in terms of seismic resistance, House 1 > House 2 > House 3 > House 4) on the nonlinear structural response. The results indicate that the record selection procedures have significant influence on the probabilistic relationship between spectral acceleration at the fundamental vibration period and maximum inter-story drift ratio, highlighting the importance of taking into account response spectral shapes in selecting and scaling ground motion records. Subjected to ground motions corresponding to the return period of 2500 years, House 1 is expected to experience very limited extent of damage; House 2 and 3 may be disturbed by minor damage; whereas House 4 may suffer from major damage occasionally. Finally, we develop statistical models of the maximum inter-story drift ratio conditioned on a seismic intensity level for wood frame houses, which is useful for seismic vulnerability assessment.
Keywords: Seismic performance; Incremental dynamic analysis; Wood-frame house; Conditional mean spectrum; Record selection; Record scaling